Bluetooth audio and video streaming on the J2ME platform - Sahd, Curtis Lee (Rhodes University, Faculty of Science, Department of Computer Science, 2011)
With the increase in bandwidth, more widespread distribution of media, and increased capability of mobile devices, multimedia streaming has not only become feasible, but more economical in terms of space occupied by the media file and the costs involved in attaining it. Although much attention has been paid to peer to peer media streaming over the Internet using HTTP and RTSP, little research has focussed on the use of the Bluetooth protocol for streaming audio and video between mobile devices. This project investigates the feasibility of Bluetooth as a protocol for audio and video streaming between mobile phones using the J2ME platform, through the analysis of Bluetooth protocols, media formats, optimum packet sizes, and the effects of distance on transfer speed. A comparison was made between RFCOMM and L2CAP to determine which protocol could support the fastest transfer speed between two mobile devices. The L2CAP protocol proved to be the most suitable, providing average transfer rates of 136.17 KBps. Using this protocol a second experiment was undertaken to determine the most suitable media format for streaming in terms of: file size, bandwidth usage, quality, and ease of implementation. Out of the eight media formats investigated, the MP3 format provided the smallest file size, smallest bandwidth usage, best quality and highest ease of implementation. Another experiment was conducted to determine the optimum packet size for transfer between devices. A tradeoff was found between packet size and the quality of the sound file, with highest transfer rates being recorded with the MTU size of 668 bytes (136.58 KBps). The class of Bluetooth transmitter typically used in mobile devices (class 2) is considered a weak signal and is adversely affected by distance. As such, the final investigation that was undertaken was aimed at determining the effects of distance on audio streaming and playback. As can be expected, when devices were situated close to each other, the transfer speeds obtained were higher than when devices were far apart. Readings were taken at varying distances (1-15 metres), with erratic transfer speeds observed from 7 metres onwards. This research showed that audio streaming on the J2ME platform is feasible, however using the currently available class of Bluetooth transmitter, video streaming is not feasible. Video files were only playable once the entire media file had been transferred.
Keywords: Bluetooth technology; Mobile communication systems; Communication -- Technological innovations; Communication -- Network analysis; Wireless communication systems; L2TP (Computer network protocol); Computer network protocols; Streaming audio; Streaming video